The Role of Gut Microbiota in Atherosclerosis and Hypertension - Ma, Junli; Li, Houkai (Frontiers in Pharmacology, 2018)
In recent years, accumulating evidence has indicated the importance of gut microbiota in maintaining human health. Gut dysbiosis is associated with the pathogenesis of a number of metabolic diseases including obesity, type 2 diabetes mellitus (T2DM), nonalcoholic fatty liver disease (NAFLD) and cardiovascular diseases (CVD). Indeed, CVD has become the leading cause of death worldwide, especially in developed countries. In this review, we mainly discuss the gut microbiota-involved mechanisms of CVD focusing on atherosclerosis and hypertension, two major risk factors for serious CVD. Then, we briefly discuss the prospects of gut microbiota-targeted therapeutic strategies for the treatment of CVD in the future.